Neutral Ligand Complexes of Alkali Metal Salts of Some Organic Acids with 2-Methyloxime - Prakash, D.; Roy, A.P.; Jafri, W.S.; Srivastava, A.K. (Asian Journal of Chemistry, 2010)
— A number of novel neutral ligand complexes having general formula ML.HL´ have been prepared where M = Li, Na or K, HL´ = 2-methyloxine. This neutral ligand complexes has been characterised on the basis of elemental analysis, IR spectral studies and conductance measurement.